Mediterranean in Dis/order Space, Power, and Identity - DI PERI, Rosita; Meier, Daniel (University of Michigan Press, 2023)
Mediterranean in Dis/order reveals the connection between space and politics by examining the role that space has played in insurgencies, conflicts, uprisings, and mobilities in the Mediterranean region. With this approach, the authors are able to challenge well-established beliefs about the power structure of the state across different disciplines (including political science, history, sociology, geography, and anthropology), and its impact on the conception, production, and imagination of space in the broader Mediterranean. Further, they contribute to particular areas of studies, such as migration, political Islam, mobilization, and transition to democracy, among others. The book, infusing critical theory, unveils original and revelatory case studies in Tunisia, Libya, Lebanon, Turkey, Syria, Morocco, and the EU Mediterranean policy, through a various set of actors and practices-from refugees and migrations policies, to Islamist or students' movements, architectural sites, or movies. This multidisciplinary perspective on space and power provides a valuable resource for practitioners interested in how space, context, and time interact to produce institutions, political subjectivities, and asymmetries of power, particularly since the turning point of the Arab uprisings. The book also helps readers understand the conditions under which the uprisings develop, giving a clearer picture about various national, regional, and international dynamics.